2022
DOI: 10.3389/fpsyt.2022.1051551
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aquatic exercise on mood and anxiety symptoms: A systematic review and meta-analysis

Abstract: ObjectiveExercise has beneficial effects on mood and anxiety symptoms. However, the impact of aquatic exercise on mood and anxiety symptoms has not been clearly confirmed. Therefore, this study aimed to synthesize and systematically analyze evidence available on boosting mental health through aquatic exercise.MethodA systematic review and meta-analysis were conducted under the PRISMA 2020 guidelines. PubMed, BIOSIS Previews, PsycINFO, Medline, SPORTDiscus, Education Source, and Web of Science Core Collection (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 59 publications
3
1
0
Order By: Relevance
“…In addition, our study suggests that anxiety levels were significantly better after swimming than those in the control group, post-intervention. A recent systematic review supports our findings, indicating that swimming exercise could significantly improve mental health and anxiety symptoms ( Tang et al, 2022b ).…”
Section: Discussionsupporting
confidence: 88%
“…In addition, our study suggests that anxiety levels were significantly better after swimming than those in the control group, post-intervention. A recent systematic review supports our findings, indicating that swimming exercise could significantly improve mental health and anxiety symptoms ( Tang et al, 2022b ).…”
Section: Discussionsupporting
confidence: 88%
“…A holistic understanding of the exercise prescription in mental health contexts demands further exploration, especially considering variables like intensity, duration, and frequency. Our findings, when juxtaposed with prior studies, suggest that the mental health effect SMD of internet-based exercise is somewhat lesser than other forms, including aquatic exercise (SMD = −0.77), [37] aerobic exercise (SMD = −0.53), [38] and Yoga. [39]…”
Section: Discussionsupporting
confidence: 78%
“…Although this is the first study focussing on menstrual and perimenopausal symptoms and cold water swimming, this finding is supported by existing literature on cold water and/or swimming and mental health improvement. 28,46,52,53 Our study supports a positive effect of cold water swimming on mental health. Multiple studies have shown higher rates of elevated mood, reduced stress and reduction in reported symptoms in outdoor swimmers, and three controlled studies finding a significant difference between the swimmers and the controls.…”
Section: Psychological Symptoms Caused By Menstruation and Perimenopausesupporting
confidence: 76%